Clouds and Silver Linings: COVID-19 Pandemic Is an Opportune Moment to Democratize Diabetes Care Through Telehealth. (November 2020) - Kerr, David; Warshaw, Hope
With the recent pivot to telehealth as a direct result of the COVID-19 pandemic, there is an imperative to ensure that access to affordable devices and technologies with remote monitoring capabilities for people with diabetes becomes equitable. In addition, expanding the use of remote Diabetes Self-Management Education and Support (DSMES) and Medical Nutrition Therapy (MNT) services will require new strategies for achieving long-term, effective, continuous, data-driven care. The current COVID-19 pandemic has especially impacted underserved US communities that were already disproportionately impacted by diabetes. Historically, these same communities have faced barriers in accessing timely and effective diabetes care including access to DSMES and MNT services, and diabetes technologies. Our call to action encourages all involved to urge US Federal representatives to widen access to the array of technologies necessary for successful telehealth-delivered care beyond COVID-19.